Policy of Reclaiming and Economic Development of the Nguyen Dynasty in CON DAO (XVII Century to the First Half of the XIX Century) - QUYET, LUU VAN; NGUYET, NGUYEN THI ANH; HUONG, NGUYEN THI MAI (The journal of contemporary issues in business and government, 2021)
Con Dao is an archipelago consisting of 16 islands, large and small, located on the sea route from West to East, from North to South in the Southeast of Vietnam today. As an archipelago with rich potentials, it is located in a very favorable geographical position in terms of geopolitics and geoeconomics, so Con Dao holds a particularly important position not only for the Nguyen Lords in the process of territorial expansion and career establishment in the South, but also Western countries (especially Britain and France) in the seventeenth and eighteenth centuries. From very early time, Westerners and Vietnamese residents in the step of finding a livelihood appeared in Con Dao to exploit products, so since the seventeenth century, the Nguyen Lords, in the process of expanding their territory to the south, have been aware of the particularly important strategic position of this archipelago, and they have implemented many policies in an organized and organized the system to conduct reclamation, economic development, and assert its sovereignty in Con Dao.